Molnupiravir compared to nirmatrelvir/ritonavir for covid-19 in high-risk patients with haematological malignancy in Europe. A matched-paired analysis from the EPICOVIDEHA registry - SİLİ, ULUHAN (My University, 2023)
Introduction: Molnupiravir and nirmatrelvir/ritonavir are antivirals used to prevent progression to severe SARS-CoV-2 infections and decrease hospitalisation and mortality rates. Nirmatrelvir/ritonavir was authorised in Europe in December 2021, whereas molnupiravir is not yet licensed in Europe as of February 2022. Molnupiravir may be an alternative to nirmatrelvir/ritonavir because it is associated with fewer drug-drug interactions and contraindications. A caveat for molnupiravir is the mode of action induces viral mutations. Mortality rate reduction with molnupiravir was less pronounced than that with nirmatrelvir/ritonavir in patients without haematological malignancy. Little is known about the comparative efficacy of the two drugs in patients with haematological malignancy at high-risk of severe COVID-19. Thus, molnupiravir and nirmatrelvir/ritonavir were compared in a cohort of patients with haematological malignancies. Methods: Clinical data from patients treated with molnupiravir or nirmatrelvir/ritonavir monotherapy for COVID-19 were retrieved from the EPICOVIDEHA registry. Patients treated with molnupiravir were matched by sex, age (±10 years), and severity of baseline haematological malignancy to controls treated with nirmatrelvir/ritonavir. Results: A total of 116 patients receiving molnupiravir for the clinical management of COVID-19 were matched to an equal number of controls receiving nirmatrelvir/ritonavir. In each of the groups, 68 (59%) patients were male; with a median age of 64 years (interquartile range [IQR] 53-74) for molnupiravir recipients and 64 years (IQR 54-73) for nirmatrelvir/ritonavir recipients; 56.9% (n=66) of the patients had controlled baseline haematological malignancy, 12.9% (n=15) had stable disease, and 30.2% (n=35) had active disease at COVID-19 onset in each group. During COVID-19 infection, one third of patients from each group were admitted to hospital. Although a similar proportion of patients in the two groups were vaccinated (molnupiravir n=77, 66% vs. nirmatrelvir/ritonavir n=87, 75%), more of those treated with nirmatrelvir/ritonavir had received four vaccine doses (n=27, 23%) compared with those treated with molnupiravir (n=5, 4%) (P<0.001). No differences were detected in COVID-19 severity (P=0.39) or hospitalisation (P=1.0). No statistically significant differences were identified in overall mortality rate (P=0.78) or survival probability (d30 P=0.19, d60 P=0.67, d90 P=0.68, last day of follow up P=0.68). Deaths were either attributed to COVID-19, or the infection was judged by the treating physician to have contributed to death. Conclusions: Hospitalisation and mortality rates with molnupiravir were comparable to those with nirmatrelvir/ritonavir in high-risk patients with haematological malignancies and COVID-19. Molnupiravir is a plausible alternative to nirmatrelvir/ritonavir for COVID-19 treatment in patients with haematological malignancy.
Keywords: Tıp; Mikrobiyoloji ve Klinik Mikrobiyoloji; Temel Eczacılık Bilimleri; Eczacılık; Yaşam Bilimleri; Sağlık Bilimleri; Temel Tıp Bilimleri; Temel Bilimler; Medicine; Microbiology and Clinical Microbiology; Basic Pharmaceutics Sciences; Pharmacology and Therapeutics; Life Sciences; Health Sciences; Fundamental Medical Sciences; Natural Sciences; Yaşam Bilimleri (LIFE); İmmünoloji; Farmakoloji ve Toksikoloji; Mikrobiyoloji; BULAŞICI HASTALIKLAR; FARMAKOLOJİ VE ECZACILIK; MİKROBİYOLOJİ; Life Sciences (LIFE); IMMUNOLOGY; PHARMACOLOGY & TOXICOLOGY; MICROBIOLOGY; INFECTIOUS DISEASES; PHARMACOLOGY & PHARMACY; Mikrobiyoloji (tıbbi); Bulaşıcı hastalıklar; Farmakoloji (tıbbi); Microbiology (medical); Infectious Diseases; Pharmacology (medical); Antiviral; COVID-19; Haematology; Malignancy; Molnupiravir; Nirmatrelvir; Ritonavir; SARS-CoV-2; Molnupiravir; Nirmatrelvir; Ritonavir; SARS-CoV-2; COVID-19; Haematology; Malignancy; Antiviral